PREPARATION AND EVALUATION OF TRANSNASAL MICROEMULSION OF VIGABATRIN - N Tarkase, Kailash; V Nimbalkar, Vikram; R Kale, Madhurima (International Journal of Clinical and Biomedical Research, 2017)
Introduction: The objective of this study was to develop novel transnasal microemulsion containing Vigabatrin for treatment of epilepsy. Method: Oleic acid was selected as oil while Tween 80 and ethanol were selected as surfactant and co-surfactant respectively based on solubility results. Optimized ratio of Tween 80 and Ethanol was selected after developing pseudoternary phase diagrams for different ratio and microemulsions were prepared. The prepared microemulsions were evaluated for globule size, viscosity, pH, and % transmittance. Ex-vivo diffusion study for optimized microemulsion was performed through goat nasal mucosa where in diffusion flux and permeability coefficients were determined. Pharmacological performance was screened in rats by electrically induced seizures. Result: It was found that op mized microemulsion was stable and transparent. Pharmacological evaluation indicated significant reduction (p<0.001) of seizures in rats treated with optimized formula on in comparison to rats treated with oral Vigabatrin microemulsion and nasal Vigabatrin solu on which suggested Vigabatrin transnasal delivery system as an effective alternate therapy for treatment of epilepsy. Conclusion: Transnasal microemulsion of Vigabatrin was successfully formulated using Tween 80 as surfactant and ethanol as co-surfactant in the formula on to treat epilepsy. Key words: Epilepsy; Transnasal Microemulsion; Vigabatrin.